Influencia del acondicionamiento en la molienda de dos variedades de sorgo (sorghum vulgare). - Romero Saldaña, Guisella Guilliana (2011)
This research deals with the study of the influence of conditioning in the grinding of two varieties of sorghum (Sorghum vulgare), one of them is commercial sorghum and other high lysine sorghum. The basic milling operations include: Cleaning, Pearl, Conditioning and grinding; the latter two being studied more closely the so harinero get the most performance. In the characterization of the raw material, the grains were red with a horny endosperm / mealy and white texture, mealy texture corresponding to commercial sorghum of a non waxy variety with aa 96 mg P / g N. 0.22 values of tannic acid for the commercial variety and 0.15 for high lysine sorghum was found, they produce dark flour, flour being high in darker lysine.